2023
DOI: 10.3390/electronics12020470
|View full text |Cite
|
Sign up to set email alerts
|

Interactivity Recognition Graph Neural Network (IR-GNN) Model for Improving Human–Object Interaction Detection

Abstract: Human–object interaction (HOI) detection is important for promoting the development of many fields such as human–computer interactions, service robotics, and video security surveillance. A high percentage of human–object pairs with invalid interactions are discovered in the object detection phase of conventional human–object interaction detection algorithms, resulting in inaccurate interaction detection. To recognize invalid human–object interaction pairs, this paper proposes a model structure, the interactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…GNN has unique advantages in modelling the interaction between the human body and objects. For example, STIGPN 12 and TMHOI 23 have successfully captured spatial and temporal variations in interaction behavior by constructing dynamic or relational graphs, enabling accurate identification of HOI behavior. Fusion of multi-modal information.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…GNN has unique advantages in modelling the interaction between the human body and objects. For example, STIGPN 12 and TMHOI 23 have successfully captured spatial and temporal variations in interaction behavior by constructing dynamic or relational graphs, enabling accurate identification of HOI behavior. Fusion of multi-modal information.…”
Section: Related Workmentioning
confidence: 99%
“…Fusion of multi-modal information. Studies by Zhang et al 24 and Fanuel et al 25 have explored fusing multi-modal information, such as vision and pose, into GNNs. The model can understand the interaction behavior more comprehensively by introducing additional information sources, thus improving detection precision.…”
Section: Related Workmentioning
confidence: 99%
“…Different research projects have studied human-object interaction detection. One example is the improvement of the accuracy while detecting interactions between persons and objects using computer vision and a graph neural network [12], or a graph model-based algorithm [13]; an application for smart glasses that assists workers in an industrial site recognizing human-object interactions [14]; as a contribution in the visual understanding field [15][16], or to help to solve the problem of missing human behavior objects [17]. It can be observed that behavior detection is related to the technologies available in the intelligent environment configuration, the sensors installed in the background, or can be related to the data sources, such as the case of images, videos, interactions with software systems [18], cameras for collecting images, microphones to record sounds within the classroom [19], and the dialogue between student and teacher and wearable devices [20] through which it is possible to identify tasks and student behavior in a classroom or digital learning environments as intelligent tutors.…”
Section: Behavior Detectionmentioning
confidence: 99%
“…In the HOIPM, we employed IR-GNN [48] to perform this task. The IR-GNN model employs a graph-based structure, enabling the effective estimation of interaction probabilities between humans and a multitude of objects.…”
Section: A Module 1: Human and Object Interaction Proposal Module (Ho...mentioning
confidence: 99%